MONITORING DAN MANAJEMEN SISTEM BATERAI MOTOR LISTRIK: MONITORING AND MANAGEMENT OF ELECTRIC MOTORCYCLE BATTERY SYSTEMS - Rahmad, Hadi; arif, saiful; Candra dewi, Kartika; Mutiara Bahtiar, Ahmad Dony; Zulfa Khalida (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2024)
Some problems that often occur with electric motorbike batteries include overcharge, overdischarge and overheat. To avoid these problems, it is necessary to regulate or monitor the battery, which is called a Battery Management System (BMS). The BMS in this research is focused on the use of PSDKU Kediri electric motors. With this BMS design, it is hoped that it can be used as a reference in battery system management so that the battery lasts longer. In this study, 112 batteries were used, consisting of 14 series and 8 parallel. The voltage sensor circuit is made to determine the battery cell voltage so that overvoltage and undervoltage protection can be carried out. Measurements can be made using a multimeter by adjusting the reading position on the voltage. The maximum voltage produced is around 57.7 volts with a charging time of 7 hours